Should I stay or should I go? A Study of Pickup Groups in Left 4 Dead 2 - Linderoth, Jonas; Björk, Staffan; Olsson, Camilla (Transactions of the Digital Games Research Association, 2014)
In this article we report an autoethnographic study of pickup groups (PUGs) in the game Left 4 Dead 2 (L4D2). The study focuses on how PUGs as social arenas are constituted by their participants and the role game design plays in structuring interaction. We use Goffman’s idea that activities are surrounded by a metaphorical frame together with an understanding of gameplay design patterns in order to analyze inclusion and exclusion, social positions and the relation between the game context and the players’ “wider worlds.” In the case of L4D2 the design pattern of Symbiotic Player Relationships creates a social situation that puts extra pressure on the players to perform well and leads to issues of identity. By negotiating the boundary between their in-game identity, based on gaming skill, and other social relations outside of the game context, players can constitute a more stable game session. The study concludes with the tentative suggestion that positive perceptions of other players’ out-of-game identity can save a game from falling apart, yet negative perceptions of other players’ values and out-of-game identities pose no threat to the game activity.